An index of the indigenous household’s representation in Mexican households’ income distribution - García-Díaz, Rocío; Gallegos-Elioza, Juan Roberto; Zenteno-García, Arturo Isaí (Papeles de Población; Vol. 23 Núm. 91 (2017), 2017)
Poverty determinants in indigenous households have an effect in labor opportunities and welfare well-being of its members. This article measures the indigenous groups’ representation in different parts of the income distribution in Mexico. We define indigenous households as those in which the head of household speaks an indigenous language. The index we obtain can be conditioned to a series of income determinants, such as, education, age, household’s composition and geographic characteristics. The representation index can be extended to measure the cost of income discrimination of indigenous groups when we weight the index by the monetary cost in pesos. The empirical analysis uses data from the Encuesta Nacional de Ingresos y Gastos de los Hogares in Mexico in 2010.